Antibacterial Effects of Silver Nanoparticles on Resistant Bacteria - Ziaee, Amadzia (Journal of Natural Sciences – Kabul University, 2021)
The antibacterial properties of silver nanoparticles have been investigated in various fields, including medicine, the textile industry, sanitary ceramics, water purification, paint, agriculture, polymer composites for both domestic and industrial applications, and water filters. The emergence of multidrug-resistant (MDR) microbes, caused by drug compounds or antibiotic resistance, is a significant factor in the survival and proliferation of microbes in harsh environments. Therefore, finding, modifying, and developing antimicrobial compounds with antibacterial potential against MDR bacteria is a critical research priority. One application of nanobiotechnology is the use of silver nanoparticles as a new material in the treatment of microbial infections. The antimicrobial properties of silver have been known since ancient times and were used in various forms to treat bacterial infections.